Phosphate (Pi) Starvation Up-Regulated GmCSN5A/B Participates in Anthocyanin Synthesis in Soybean (Glycine max) Dependent on Pi Availability - Xiaohui Mo (MDPI AG, 2021)
Phosphorus (P) is an essential macronutrient for plant growth and development. Among adaptive strategies of plants to P deficiency, increased anthocyanin accumulation is widely observed in plants, which is tightly regulated by a set of genes at transcription levels. However, it remains unclear whether other key regulators might control anthocyanin synthesis through protein modification under P-deficient conditions. In the study, phosphate (Pi) starvation led to anthocyanin accumulations in soybean (Glycine max) leaves, accompanied with increased transcripts of a group of genes involved in anthocyanin synthesis. Meanwhile, transcripts of GmCSN5A/B, two members of the COP9 signalosome subunit 5 (CSN5) family, were up-regulated in both young and old soybean leaves by Pi starvation. Furthermore, overexpressing GmCSN5A and GmCSN5B in Arabidopsis thaliana significantly resulted in anthocyanin accumulations in shoots, accompanied with increased transcripts of gene functions in anthocyanin synthesis including AtPAL, AtCHS, AtF3H, AtF3′H, AtDFR, AtANS, and AtUF3GT only under P-deficient conditions. Taken together, these results strongly suggest that P deficiency leads to increased anthocyanin synthesis through enhancing expression levels of genes involved in anthocyanin synthesis, which could be regulated by GmCSN5A and GmCSN5B.